Design and synthesis of biphenyl and biphenyl ether inhibitors of sulfatases. Issue 4 (25th January 2016) - Reuillon, Tristan; Alhasan, Sari F.; Beale, Gary S.; Bertoli, Annalisa; Brennan, Alfie; Cano, Celine; Reeves, Helen L.; Newell, David R.; Golding, Bernard T.; Miller, Duncan C.; Griffin, Roger J.
Abstract : Two series of inhibitors of sulfatase 2, ARSA and ARSB were designed based on biphenyl and biphenyl ether scaffolds substituted with e.g. sulfamate and carboxylate groups. Abstract : Inhibitors of sulfatase-2 are putative anticancer agents, but the discovery of potent small molecules targeting this enzyme has proved challenging. Based on molecular modelling, two series of sulfatase-2 inhibitors have been developed with biphenyl and biphenyl ether scaffolds judiciously substituted with sulfamate, carboxylate and other polar groups ( e.g. amino). Inhibition of aryl sulfatase A and B was also determined. The biphenyl ether derivatives were less selective for sulfatase-2 over aryl sulfatase B than the biphenyl series. All biphenyl ether derivatives inhibited aryl sulfatase A, whereas only amino derivatives inhibited aryl sulfatase B significantly. In the biphenyl series few derivatives exhibited activity against aryl sulfatase B. The trichloroethylsulfamate group was identified as a new pharmacophore enabling potent inhibition of all of the sulfatases studied.